Enhancing corrosion resistance of ZK60 magnesium alloys via Ca microalloying: The impact of nanoscale precipitates - Wei Fu; Hejie Yang; Tianshu Li; Jiapeng Sun; Shengwu Guo; Daqing Fang; Weichao Qin; Xiangdong Ding; Yimin Gao; Jun Sun (Journal of Magnesium and Alloys, 2023)
Enhancing corrosion resistance of Mg-Zn alloys with high strength and low cost was critical for broadening their large-scale practical applications. Here we prepared solutionized, peak- and over-aged ZK60 alloys with and without microalloying Ca (0.26 wt.%) to explore the effects of nanoscale precipitates on their corrosion behavior in detail via experimental analyses and theoretical calculations. The results suggested the peak-aged ZK60 alloy with Ca addition showed improved corrosion resistance in comparison with the alloys without Ca, owing to the contribution of Ca on the refinement of precipitates and increase in their number density. Although the precipitates and Mg matrix formed micro-galvanic couples leading to dissolution, the fine and dense precipitates could generate “in-situ pinning” effect on the corrosion products, forming a spider-web-like structure and improving the corrosion inhibition ability accordingly. The pinning effect was closely related to the size and number density of precipitates. This study provided important insight into the design and development of advanced corrosion resistant Mg alloys.